The hour complete series 1 & 2 - Giorgetti, Daniel 1971-; Sargent, Kevin (2entertain, 2012)
Series one: "London, 1956. At Lime Grove Studios, the BBC are launching The Hour, a new topical news programme. At the heart of the show are three contrasting journalists: enigmatic producer Bel Rowley (Romola Garai), a spirited woman in a mans world; her best friend Freddie Lyon (Ben Whishaw), a brilliant and passionate reporter; and a charming, well-connected front man, Hector Madden (Dominic West). As Freddie moves to cover a significant but controversial breaking story, the trio become entangled in an intense interplay of politics, ambition and romance, ignited by a mysterious murder and chilling conspiracy. Fifties London is brought to life in this tense drama, delivering an exquisite and stylish portrayal of a world on the threshold of momentous change"-- Series two: "Re-joining The Hour a year on in 1957, the team are still striving to broadcast the stories they believe in, grappling with the disturbing threat of the Cold War and a country in the grip of unsettling, rapid change. Bel (Romola Garai) is still single and determined not to get involved with another married man, but finds herself taking on her adversary Bill Kendall (Tom Burke), an ITV producer whose magnetic charm she cannot help but find irresistible. Hector (Dominic West) has risen to the status of a national celebrity and, drawn into the seductive glamour of Soho nightclub El Paradis, falls under the spell of the beautiful and seductive Kiki (Hannah Tointon). No longer happy at The Hour under Randalls (Peter Capaldi) new regime, he is tempted by offers from ITV, but when a night at the club goes badly wrong, scandal threatens and Hector must try and stop a news story that could destroy his marriage and his career. Investigative reported Freddie (Ben Whishaw) makes an unexpected return to uncover and tackle police corruption within the world of Soho crime and vice". [Container]
Bildformat 16:9 (anamorph)
Orig.: Großbritannien 2011 - 2012
Enth. series 1: Creating "The hour" - set design piece ; behind the scenes of "The hour". Series 2: Behind the scenes of "The hour"